Debating the drug war: race, politics, and the media - Rosino, Michael L. (Framing 21st century social issues, 2021)
"This book traces how the history between race, drug policies, and the role of the media reflects dominant ideas about race, crime, politics. Through 30 years of newspaper reports and online commentary, Rosino shows how people form identities in a debate that heavily influences politics, public policies, and race relations"--